Neuroprotective effects of Ficus deltoidea in Alzheimer’s disease-like rat model: insights from behavior, histology, and amyloid pathology - Usman, Abdulhamid Sani; Manoharan, Sushmitaa Dhevii; Che Mohd Nassir, Che Mohd Nasril; Abdul Hamid, Hafizah; Hein, Zaw Myo; Norazit, Anwar; Murthy, Jayakumar; Zainol, Murizal; Kamaruzzaman, Mohd Amir; Chiroma, Samaila Musa; Mustapha, Muzaimi; Mohd Moklas, Mohamad Aris; et al. (Springer, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder marked by cognitive decline, memory impairment, and accumulation of amyloid-β (Aβ) plaques. While current treatments offer limited efficacy, medicinal plants such as Ficus deltoidea (FD), a traditional remedy, have shown promise due to their neuroprotective and anti-inflammatory properties. An AD-like phenotype was induced in male Wistar rats using D-galactose and aluminum chloride over 70 days. FD extract was administered orally at 50, 100, and 200 mg/kg. Spatial memory was evaluated using the T-maze test. Histological analyses of the hippocampi’s Cornu Ammonis 1 and 3 (CA1 and CA3) regions were conducted via hematoxylin and eosin (H&E) staining, and Aβ plaques deposition was assessed with Congo red. Enzyme-linked immunosorbent assay (ELISA) was used to quantify hippocampal levels of Aβ (1–42) and β-secretase-1 (BACE-1). FD treatment significantly enhanced spatial memory, preserved pyramidal neuron integrity in CA1 and CA3, and reduced amyloid plaque formation. Biochemically, FD markedly decreased hippocampal Aβ (1–42) and BACE-1 concentrations in a dose-dependent manner. Thus, FD exhibits multi-target neuroprotective effects in an AD-like model, potentially via modulation of amyloidogenic pathways. Further studies are warranted to explore its mechanisms and therapeutic potential in other brain regions implicated in AD.